Human Factors in Green Building - Zhonghua Gou (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
World Green Building Council suggests that health, well-being and productivity should be the next chapter for green building. There is an obvious shift of green building movement from technology-centric towards human-centric, which culminates in recent WELL Building Standard, focusing exclusively on human health and wellness. This special issue aims to push forward the research, discourse and practice of green building towards more human-oriented design solutions. Particularly, this special issue collects papers on: Post-occupancy evaluation of green buildings Indoor Environmental Quality (IEQ) Thermal Comfort and Adaptive Behaviors Quality of Life and Housing Healthcare Design